Authentic Text-Based Activities to Enhance Students’ Ability in Using Perfect Verb Tenses - M. Valdez, Christian Jay; G. Cardenas, Princess Lou; Aurelio, Alpha Y.; G. Adisas, Mark Andrei; Villanueva, Louie (Universitas Islam Negeri Alauddin Makassar, 2023)
This research incorporated authentic-text based activities as an intervention to enhance Grade 8 students’ usage of perfect verb tenses in English Class. Specifically, it identified the students’ level of ability in using perfect verb tenses through a pretest and posttest. In order to attain these aims, the study used both qualitative and quantitative data collection methods. Descriptive and inferential statistics were performed to make sense of the gathered data. Overall, this study confirms that authentic-text based activities is effective as demonstrated by its posttest mean score (10.27) or Satisfactory level compared to the pretest mean score (4.20) or Fair level, which meant that there was a mean difference of 6.07. Moreover, the t-value of -31.937 meant that the pretest obtained a lower result than the posttest. In addition, the p-value of 0.000 is less than the 0.01 level of significance which further validates that there is a significant difference of the pretest and posttest. This implies that the intervention of this research proved to enhance the ability of Grade 8 students at Ilocos Norte National High School in using perfect verb tenses. Thus, the intervention of this study is highly recommended to Grade 8 students of other schools because authentic-text based activities can be contextualized to accommodate the varied conditions and needs of different subjects in Philippine basic education.